Partnering for Impact: Jameel Observatory's 5th Annual Community of Practice on Anticipatory Action in Africa's Drylands - Grossi, Amanda; Ahmed, Jemal Seid; Degefie, Degefie Tibebe; Demissie, Teferi (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
In May 2025, the Jameel Observatory held its fifth Community of Practice workshop—its first ever in Ethiopia—at ILRI in Addis Ababa. With support from the AICCRA project, which helped convene key national stakeholders, the workshop focused on advancing early warning and anticipatory action for dryland resilience. The event aligned closely with AICCRA’s Theme 4 on Climate Information Services, emphasizing equitable access to climate data, capacity-building for next users, and inclusion of pastoralist communities. Over 100 participants engaged across sessions exploring resilience, forecasts, locally led action, and data use. Two featured sessions examined Ethiopia’s role in the Early Warning for All (EW4All) initiative and explored the role of capacity development in advancing locally led adaptation. The event reinforced AICCRA’s goals to strengthen national and regional systems, promote anticipatory action, and empower advisory service providers to make climate information actionable across Africa’s drylands.